Studying of features of information exchange of participants of the pharmaceutical market - E I Gribkova (RUDN Journal of Medicine, 2013)
Qualitatively provided information and correctly chosen means commodity information have positive impact on process of decision-making on purchase by the visitor of a drugstore. For effective modeling of this process it is necessary to consider motives of the address to a drugstore, target audience, the purpose of providing commodity information. Development of models of consecutive behavior helps to increase quality of the pharmaceutical help and competitiveness of the pharmaceutical organization.